Tourism development and community response : the case of the Inhambane Coastal Zone, Mozambique - Nhantumbo, Emídio Samuel (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2009.